Influence of Neonatal Resuscitation Training on Practice of Community Health Extension Workers in Managing Asphyxiated Newborns in Rural Nigeria: A Qualitative Study - Adenike Adebola O. Olaniyi MPh, RN; Busisiwe P. Ncama PhD, MCur (SAGE Publishing, 2020)
Birth asphyxia is a global health burden, and effective neonatal resuscitation could reduce the burden of deaths. Providing a suitable newborn resuscitation care will depend on the availability of an effective skilled health worker, who is competent in neonatal resuscitation. The study explores and assesses the effect of neonatal resuscitation training and retention of knowledge and skills in the management of asphyxiated newborns in rural Nigeria. This study used a narrative analysis technique to analyze data from a semistructured, individual interview. Data were analyzed using ATLAS.ti 8 qualitative software and applying the principle of thematic analysis. There was a considerable retention of knowledge and ability to practice the procedure even though some equipment was not available. Proficiency in neonatal resuscitation is an essential intervention for the survival of newborns and infants. Therefore, execution of neonatal resuscitation training program in rural communities can further improve knowledge and skills of community birth attendants in Nigeria.